Gatekeeping Fake News Discourses on Mainstream Media Versus Social Media. (December 2019) - Al-Rawi, Ahmed
This study analyzes mainstream media (MSM) coverage of fake news discourse and compares it with social networking sites (SNS) users who reference the term "fakenews" in their tweets. The study employs computational methods by analyzing over 8 million tweets and 1, 350 news stories using topic modeling. Building on the theory of (networked) gatekeeping and Herman and Chomsky's propaganda model, the results show that SNS users follow networked gatekeeping practices by mostly associating fake news references to the alleged bias of MSM. On the other hand, MSM coverage tends to link fake news to SNS's negative role in spreading misinformation. I argue here that there is a networked flak activity on Twitter which is defined as a collective negative response to MSM in order to discipline it, change its tone and editorial stance, or undermine the public's trust in it.